Osteogenic/Odontogenic Bioengineering with co-Administration of Simvastatin and Hydroxyapatite on Poly Caprolactone Based Nanofibrous Scaffold - Mohammad Samiei; Marziyeh Agazadeh; Effat Alizadeh; Naser Aslaminabadi; Soodabeh Davaran; Sajjad Shirazi; Farhad Ashrafi; Roya Salehi (Tabriz University of Medical Sciences, 2016)
Purpose: Statin is an effective factor for promoting osteogenesis. The aim of the present study was to evaluate the effect of simvastatin (SIM) and/or HA addition on changes in osteogenesis levels by human DPSCs transferred onto three-dimensional (3D) nanofibrous Poly (ε-caprolactone) (PCL)/Poly lactic acide (PLLA) polymeric scaffolds. Methods: For this purpose, a 3D nanofibrous composite scaffold of PCL/PLLA/HA was prepared by electrospinning method. SIM was added to scaffolds during DPSCs culturing step. Cell proliferation and osteogenic activity levels were assessed by using MTT assay and Alizarin Red assay methods. In addition, the expression of genes responsible for osteogenesis, including BMP2, Osteocalcin, DSPP and RUNX2, were determined before and 2 weeks after incorporation of SIM. Results: The MTT assay showed that PCL/PLLA/HA scaffolds seeded with DPSCs has significant (p<0.05) more proliferative effect than PCL/PLLA or DMEM cultured cells, additionally SIM administration improved this result over the PCL/PLLA/HA scaffolds without SIM treatment. SEM imaging revealed improved adhesion and probably osteogenic differentiation of DPSCs on PCL/PLLA/HA nanofibers treated with SIM, moreover the alizarin red assay ensured significant (p<0.05) higher mineralization of this group. Finally, real time PCR confirmed the positive regulation (P<0.05) of the expression of osteo/odontogenesis markers BMP2, Osteocalcin, DSPP and RUNX2 genes in PLLA-PCL-HA (0.1)-SIM group. Conclusion: As a result, addition of simvastatin with incorporation of hydroxyapatite in PCL-PLLA scaffolds might increase the expression of osteogenesis markers in the DPSCs, with a possible increase in cell differentiation and bone formation.